2014
DOI: 10.1037/a0037319
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dimensions of administrative support for play therapy in schools.

Abstract: While play therapy with young children has empirical support, it has been underutilized in public elementary school settings due to multiple individual and systemic barriers, which are indirectly or directly influenced by school administrator support. The purpose of this qualitative study was to explore the experiences and perceptions of administrative support from the perspectives of elementary public school counselors and social workers known to use play therapy. Using a directed content analysis approach, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…If one is fortunate enough to find a play therapy supervisor the additional challenge of finding one who is attuned to the school counseling culture and role ought to be noted. Additionally, Peabody (2014) found that though there was administrative support for play therapy, administrators did not understand the difference in administrative and clinical supervision; as a result, they did not provided resources for clinical supervision. A major implication of this research is the need to strengthen both the knowledge about play therapy and supervision experiences of elementary school counselors.…”
Section: Discussionmentioning
confidence: 99%
“…If one is fortunate enough to find a play therapy supervisor the additional challenge of finding one who is attuned to the school counseling culture and role ought to be noted. Additionally, Peabody (2014) found that though there was administrative support for play therapy, administrators did not understand the difference in administrative and clinical supervision; as a result, they did not provided resources for clinical supervision. A major implication of this research is the need to strengthen both the knowledge about play therapy and supervision experiences of elementary school counselors.…”
Section: Discussionmentioning
confidence: 99%
“…The community-of-practice group generated other topics of shared interest throughout the year, leading to role clarification, cofacilitation of social-skill groups, and interprofessional presentations at respective discipline-specific conferences. Socially constructed emotional support was increased to offset the feelings of isolation that often result as being the only one in his or her respective role within a school context (Peabody, 2014). The community-of-practice model offered the early-childhood therapists mutually collaborative relationships that positioned them to offer support to each other.…”
Section: Strategies and Modelsmentioning
confidence: 99%
“…Investigations of supervision processes in the specialty area of play therapy have been conducted (Allen, Folger, & Pehrsson, 2007; Blanco, Muro, & Stickley, 2014; Ray & Neill, 2006). Specific examples include knowledge of advanced play therapy skills (Ray, 2004), play therapy in school settings (Peabody, 2014), perceived training needs of supervisors (Fall, Drew, Chute, & Moore, 2007), understanding genuineness (Blanco et al, 2014), and multicultural competence (Penn & Post, 2012). These studies support the development of play therapy supervision.…”
Section: Review Of Literaturementioning
confidence: 99%